The Effect of Calcium Silicate on The Phosphorus Sorption Characteristics of Andisols Lembang West Java - Arief Hartono (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2008)
The effect of calcium silicate CaSiOJ the phosphorus (P) sorption characteristics were studied in Andisols Lembang.The amount of 0, 2.5 and 5% CaSiOJ (calcium silicate) or 0, 7.5 and 15 g calcium silicate per pot was added to the 300 g(oven-dry weight) soil and incubated for one month. A completely randomized design in double replication was set up. After one month incubation, P sorption and P sorption kinetic experiments were conducted The results of P sorption experiment showed that P sorption data were satisfactorily described by the Langmuir equation. which was used to determine P sorption maxima, bonding energies and P sorbed at 0.2 mg P £